2015
DOI: 10.1007/s00401-015-1504-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent defects of alpha-synuclein oligomer uptake in microglia and monocytes

Abstract: Extracellular alpha-synuclein (αsyn) oligomers, associated to exosomes or free, play an important role in the pathogenesis of Parkinson's disease (PD). Increasing evidence suggests that these extracellular moieties activate microglia leading to enhanced neuronal damage. Despite extensive efforts on studying neuroinflammation in PD, little is known about the impact of age on microglial activation and phagocytosis, especially of extracellular αsyn oligomers. Here, we show that microglia isolated from adult mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 67 publications
11
95
0
1
Order By: Relevance
“…Recently, it could be demonstrated that cultured microglia from adult mice displayed a less efficient uptake and clearance of oligomeric α-synuclein as compared to younger mice. Similar effects could be demonstrated when analyzing peripheral monocytes from older vs. younger human subjects (Bliederhaeuser et al, 2016). Taken together, these findings suggest that there might be an age-dependent deficit in the uptake and clearance of toxic α-synuclein by phagocytic cells.…”
Section: Proposed Mechanisms Behind α-Synuclein Mediated Toxicitysupporting
confidence: 66%
“…Recently, it could be demonstrated that cultured microglia from adult mice displayed a less efficient uptake and clearance of oligomeric α-synuclein as compared to younger mice. Similar effects could be demonstrated when analyzing peripheral monocytes from older vs. younger human subjects (Bliederhaeuser et al, 2016). Taken together, these findings suggest that there might be an age-dependent deficit in the uptake and clearance of toxic α-synuclein by phagocytic cells.…”
Section: Proposed Mechanisms Behind α-Synuclein Mediated Toxicitysupporting
confidence: 66%
“…Furthermore, in a mouse model of Alzheimer’s disease, the phagocytic capacity of microglia was reduced and inversely correlated to the Aβ plaque burden, suggesting that microglia function declined with severity of disease (Krabbe et al, 2013). Similar defective phagocytic activity was described in aged mice whereby primary microglia isolated from aged mice had less effectively taken up exosome associated α-synuclein oligomers compared to microglia from young mice (Bliederhaeuser et al, 2015). On the contrary, results from other studies in animal models of PD have suggested long-term phagocytic activation of microglia (Barcia et al, 2013; Rodriguez et al, 2007).…”
Section: Introductionsupporting
confidence: 60%
“…This observation might be explained by age-dependent microglia deficits. Indeed, isolated microglia from adult mice display phagocytosis impairment of free and exosome-associated αSyn oligomers associated with enhanced TNFα secretion (Bliederhaeuser et al, 2016). Taken together, the contribution of aged microglia to the progressive nature of PD is most likely and the fact that the nigrostriatal system displays a high density of microglia (Sharaf et al, 2013) further supports the hypothesis that microglia are involved in PD pathogenesis.…”
Section: Aging and Ad And Pdmentioning
confidence: 99%